Resistance Testing of Escherichia Coli Bacteria Producing Extended Spectrum Beta-Lactamase (ESBL) in Urinary Tract Infection (UTI) Patients at Indramayu Regional General Hospital - Zakia*, Fitri; Karsidin, Bambang; Basri, Ade Hasan (Universitas Syiah Kuala, 2024)
Urinary Tract Infection (UTI) is an infection caused by the growth of microorganisms in the human urinary tract. The bacteria Escherichia coli can cause UTIs. Escherichia coli is a bacterium that can become resistant to antibiotics in UTIs because it produces the Extended-Spectrum -lactamase (ESBL) enzyme. ESBL causes high morbidity and mortality because it can make it challenging to manage infectious diseases. Research on ESBL-producing bacteria has been carried out in several hospitals in Indonesia. The difference in place and time of research causes the pattern of resistance of UTI-causing bacteria to antibiotics to be different. The samples in this study were urine specimens from patients with UTI diagnoses who were examined for culture at the microbiology laboratory of Indramayu Hospital. The sampling technique in this study is the total sampling method. The research method used is Quantitative Descriptive. Bacteria identification and Resistance tests were carried out using the Vitec 2 Compact tool. The data obtained from the research results are then collected in tables and used as a reference in the preparation of data analysis. Escherechia coli is the most common type of bacterial species, at 41%. Ampicillin is 100% resistant to all isolates, and Meropenem and Ertapenem are 100% sensitive. Penicillin MIC value for Sensitive outcomes 4; Intermediate 16; and Resistant 32. Cephalosporin group MIC value for Sensitive results 4; Intermediates 8; and Resistant 64. Carbapenem group MIC value for Sensitive 0.5; Intermediates 8; and Resistant 64. Identification of ESBL Escherichia coli bacteria is 89% ESBL positive and 11% ESBL negative.